Novel exonic mutation inducing aberrant splicing in the IL10RA gene and resulting in infantile-onset inflammatory bowel disease: a case report. Issue 1 (December 2016) - Yanagi, Tadahiro; Mizuochi, Tatsuki; Takaki, Yugo; Eda, Keisuke; Mitsuyama, Keiichi; Ishimura, Masataka; Takada, Hidetoshi; Shouval, Dror; Griffith, Alexandra; Snapper, Scott; Yamashita, Yushiro; Yamamoto, Ken
Abstract Background Although deleterious mutations in interleukin-10 and its receptor molecules cause severe infantile-onset inflammatory bowel disease, there are no reports of mutations affecting this signaling pathway in Japanese patients. Here we report a novel exonic mutation in theIL10RA gene that caused unique splicing aberrations in a Japanese patient with infantile-onset of inflammatory bowel disease in association with immune thrombocytopenic purpura and a transient clinical syndrome mimicking juvenile myelomonocytic leukemia. Case presentation A Japanese boy, who was the first child of non-consanguineous healthy parents, developed bloody diarrhea, perianal fistula, and folliculitis in early infancy and was diagnosed with inflammatory bowel disease. He also developed immune thrombocytopenic purpura and transient features mimicking juvenile myelomonocytic leukemia. The patient failed to respond to various treatments, including elemental diet, salazosulfapyridine, metronidazole, corticosteroid, infliximab, and adalimumab. We identified a novel mutation (c.537G > A, p.T179T) in exon 4 of theIL10RA gene causing unique splicing aberrations and resulting in lack of signaling through the interleukin-10 receptor. At 21 months of age, the patient underwent allogeneic hematopoietic stem cell transplantation and achieved clinical remission. Conclusions We describe a novel exonic mutation in theIL10RA gene resulting in infantile-onset inflammatory bowel disease. This mutation might also be involved in his early-onset hematologic disorders. Physicians should be familiar with the clinical phenotype of IL-10 signaling defects in order to enable prompt diagnosis at an early age and referral for allogeneic hematopoietic stem cell transplantation.